Smear layer removal and erosion on the substrate using different acid solutions - Labarta, Alicia Beatriz (2018)
Objetive: Evaluate with scanning electron microscope (SEM) smear layer removal and erosion on the sustrate, while irrigating the roots canals with four acid solutions. Methods: Were used 30 unirradicular mandibular premolars divided in five groups according to the type of irrigation: Control Group 1: NaOCl 5.25%. Group 2: 5.25% NaOCl + 17% ethylenediaminetetraacetic acid (EDTA). Group 3: 5.25% NaOCl + 5% maleic acid. Group 4: 5.25% NaOCl + 10% citric acid Group 5: 5.25% NaOCl + 37% fosforic acid. Ninety microphotographs were performed with SEM at 5000x at 2, 6 and 10 mm of the working length. Results: There was significant difference in the removal of smear layer between the control group and other groups (p<0.05). There was significant difference between group 4 and groups 2 and 5. There was no significant difference between groups 3 and 4, nor groups 2, 3 and 5. There was no significant difference in removal reabetween thirds of root canals (p=0.07). About erosion, there was no significant difference between irrigants (p<0.05). No significant differences were found between thirds of root canals (p=0.19). Conclusions: 5.25% NaOCl + 5% maleic acid and 5.25% NaOCl + 10% citric acid produce most smear layer removal. 5.25% NaOCl + 37% phosphoric acid and 5.25% NaOCl + 10% citric acid produce greater erosion. There was no difference of smear layer removal nor erosion between thirds of root canal. Combination of 5.25% NaOCl + 5% maleic acid would provide better balance between removal capacity and erosion degree.